HEMIBALLISMUS: A RARE PRESENTATION OF UNCONTROLLED DIABETES MELLITUS TYPE 2 - Macrohon , Calvin Rei; Kanapi , Maria Princess (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Diabetic striatopathy is a rare acute movement disorder with a prevalence of 1 in 100,000. This is characterized by sudden, non-purposeful jerking movements secondary to non-ketotic hyperglycemia. We report a case of an 80-year-old female with type 2 diabetes who came in due to right-sided hemiballism with behavioral changes. Initial blood glucose was elevated with normal serum ketones. Glycated hemoglobin (HbA1c) was 13.7%, consistent with poorly controlled diabetes mellitus. On evaluation, T1-weighted hyperintensity signals involving the left lentiform nucleus were seen on magnetic resonance imaging, which was suggestive of diabetic striatopathy. She was given insulin therapy for glucose control and supportive medical management for the neurologic symptoms. Symptom relief was achieved on the third hospital day after good glycemic control was attained. Proper identification and diagnosis are essential in managing diabetic striatopathy, with adequate glycemic control as the most effective therapeutic management.